DEVELOPMENT OF STUDENT WORKSHEET ON PROBABILITY WITH REALISTIC MATHEMATICS EDUCATION APPROACH USING PANDEMIC CONTEXT - Dava Imadul Bilad; Rooselyna Ekawati (MATHEdunesa, 2022)
The condition of education during the pandemic experienced several changes that made it difficult for students to understand the material being taught and made them more passive in learning activities.Therefore, this study aim at developing student worksheet on probability material with realistic mathematics education approach with pandemic context to help students learn the material well and increase student activity in distance learning and make learning activities more meaningful for students because it makes students find their own concepts so that students can better understand the material well. This study based on 4 aspects, namely: validity, practicality, effectiveness, and feasibility. This research was developed following the ADDIE principle (Analysis, Design, Development, Implementation, and Evaluation) and the subject for this study was 8th grade students. Then this student worksheet was validated by 2 experts and supervised for practicality by 1 expert. The results of developing student worksheets have a validity value of 83.78% and considered as few revisions. Then for the practicality test, it gets a score of 85% and categorized as practical. Then for the learning results, in the pre-test most students have not been able to work on the questions given and in the post-test all students can work on the questions given well so that the success of student worksheets is very high to make students understand the concept. The student satisfaction questionnaire in learning, the average value of 4.8 can be rounded up to 5, which means that students are very satisfied with the learning activities that have been carried out. So, the result of this research is the success of developing learning media on the material of probability that is suitable to be given to students during this pandemic because it can improve student’s understanding of material and make students more active in participating in learning activities. Keywords: Student Worksheet; Realistic Mathematics Education (RME); ADDIE (Analysis, Design, Development, Implementation, And Evaluation); Probability.